Case Report: Afatinib Sensitivity in Rare EGFR E746_L747delinsIP Mutated LUAD With Peritoneal Metastases - Zhang, Lili; Yang, Lu; Sun, Binxu; Deng, Yixiao; Yang, Jie; Wu, Dongfang; Kong, Fanming (Frontiers in Oncology, 2022)
Patients with non-small cell lung cancer harboring the epidermal growth factor receptor (EGFR)-sensitive mutations are known to benefit significantly from EGFR tyrosine kinase inhibitors (TKIs), such as erlotinib, gefitinib, icotinib, or afatinib. However, the efficacy of EGFR-TKIs against rare mutations has not yet been well investigated. Here, we report a female patient with advanced lung adenocarcinoma (LUAD), carrying a rare mutation of EGFR Exon19 E746_L747delinsIP, who was administered first-generation EGFR-TKIs as the first-line treatment. The patient continued to progress slowly until peritoneal metastases have occurred. Subsequently, the patient was treated with anlotinib for 5 months until disease progression. Given the finding of the same EGFR rare mutation in peritoneal effusion without other EGFR-TKI resistance mutations, the patient received afatinib with a tremendous response. Our results may be of clinical relevance for patients with LUAD carrying this rare mutation, and these findings warrant further investigation.